Pretreatment with an anti-CGRP monoclonal antibody attenuates mild TBI-induced tactile hypersensitivity in mice - Anne-Sophie Wattiez; Adisa Kuburas; William C. Castonguay; Kim Fejgin; Ib V. Klewe; Andrew F. Russo (The Journal of Headache and Pain)
Abstract Background Post-traumatic headache (PTH) can develop following a mild traumatic brain injury (mTBI), such as a concussion. It is especially common among active-duty military personnel, Veterans, and athletes. The high prevalence and chronic nature of PTH highlight the importance of studying these conditions in animal models to develop new, effective treatments. Since the symptoms associated with PTH resemble those of migraine, we focused on the neuropeptide calcitonin gene-related peptide (CGRP) as a potential therapeutic target. Methods We used a mouse model of mTBI involving three repeated closed head impacts to assess the therapeutic efficacy of a monoclonal antibody (mAb) that blocks CGRP. To validate the model, we first assessed and optimized the development of periorbital and plantar tactile hypersensitivity in outbred CD1 mice. We then tested these responses after intraperitoneal injection of two migraine triggers: CGRP and sodium nitroprusside (SNP), a nitric oxide donor. Then, we assessed the efficacy of the anti-CGRP mAb using different administration paradigms. Results Early administration of an anti-CGRP mAb before induction of TBI did not fully prevent the initial transient periorbital tactile hypersensitivity observed following multiple closed head injuries. However, the mAb did partially reduce persistent periorbital tactile hypersensitivity to a sub-threshold trigger. Administration of the mAb immediately after the injuries was also able to partially reduce persistent hypersensitivity. Importantly, injection of the anti-CGRP mAb 24 h prior to injection of a sub-threshold dose of CGRP or SNP fully prevented periorbital hypersensitivity to these triggers during the persistent sensitivity phase. Conclusions These results indicate that an anti-CGRP mAb can partially, but not fully, attenuate cephalic tactile hypersensitivity when administered immediately before or after the mTBI event. In contrast, a stronger rescue was seen when the anti-CGRP mAb was administered just prior to CGRP and nitric oxide triggers. Thus, depending on the timing of administration, the anti-CGRP mAb can block persistent sensitization to headache triggers after mTBI.